TDPAC characterization of tin oxides using 181Ta - Moreno, Mario Sergio Jesús (1991)
In connection with a general study of the evolution of tin-oxygen thin films, we report here on the hyperfine interactions of181Ta substitutionally replacting tin in the isolated phases SnO and SnO2. For this purpose, pure SnO pressed powder and a thin SnO2 film were implanted with181Hf. In both cases, unique quadrupole frequencies were found after thermal annealing treatments. The results indicate that the following hyperfine parameters: υ; Q; = 740.6(2.1) MHz, η=0.07(2) and υ; Q; = 971.5(1.9) MHz, η=0.72(1) characterize181Ta in SnO and SnO2, respectively.